2013
DOI: 10.1371/journal.pone.0057866
|View full text |Cite
|
Sign up to set email alerts
|

Molecules Altering the Intracellular Thiol Content Modulate NF-kB and STAT-1/IRF-1 Signalling Pathways and IL-12 p40 and IL-27 p28 Production in Murine Macrophages

Abstract: BackgroundThe aim of this study was to investigate the molecular mechanisms involved in the production of Th1 cytokines, namely IL-12 and IL-27, when the intra-macrophage redox state was altered by different chemical entities such as GSH-C4, which is reduced glutathione carrying an aliphatic chain, or I-152, a pro-drug of N-acetyl-cysteine (NAC) and beta-mercaptoethylamine. We had already demonstrated that GSH-C4 and I-152 could shift the immune response towards Th1 in Ovalbumin-immunized mice as well as enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 50 publications
0
45
0
1
Order By: Relevance
“…Determination of the amount of thiol in peritoneal macrophages was performed as previously described (47). The removed macrophages were immediately lysed with 100 l of lysis buffer (0.1% Triton X-100, 0.1 M Na 2 HPO 4 , 5 mM EDTA, pH 7.5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Determination of the amount of thiol in peritoneal macrophages was performed as previously described (47). The removed macrophages were immediately lysed with 100 l of lysis buffer (0.1% Triton X-100, 0.1 M Na 2 HPO 4 , 5 mM EDTA, pH 7.5).…”
Section: Methodsmentioning
confidence: 99%
“…Peritoneal exudate cells of B6 mice were obtained by peritoneal lavage as previously described (47). Macrophages were incubated for 24 h in 35-mm-diameter dishes with RPMI 1640 medium (Sigma) supplemented with 10% heat-inactivated fetal bovine serum (EuroClone), 2 mM L-glutamine, 100 U/ml penicillin, and 100 g/ml streptomycin (Sigma) and then processed differently according to the determinations that were to be made.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that IL-27 is a member of IL-12 family cytokines that is composed of IL-27p28 and Epstein-Barr virus induced gene 3 (EBI3) [1,[5][6][7]. The IL-27 receptor that consists of WSX-1 and gp130 and is required for all established signaling pathways initiated IL-27 [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…As células T helper tipo 1 (Th1), secretam citocinas pró-inflamatórias, como por exemplo, TNF-α e IL-1β, e ao contrário, as células T helper tipo 2 (Th2) secretam interleucinas anti-inflamatórias (IL-4, IL-10), promovendo com isso um feedback positivo. 39,45,46,47,48 Outro fator importante é a fagocitose de células apoptóticas por macrófagos e células dendríticas e com isto, estas células estimulam a tolerância imune ao induzir a liberação de citocinas anti-inflamatórias, incluindo a IL-10 e TGF-β, o qual suprimi a secreção de citocinas pró-inflamatórias. Esta potente ligação entre a liberação de IL-10 pela apoptose das células e a imunossupressão na sepse é preditiva de um desfecho fatal em pacientes críticos.…”
unclassified